Export performance of Indian Seafood Industry - a study on MPEDA Cochin - Deepthi Babu (College of Co-operation Banking and Management, 2017)
Fish producing countries, apart from meeting the demand in domestic market, are exporting fish products to many countries to meet the demand in international market and also to earn foreign exchange. There are several items in the category of marine products which is meant for export of major destinations of the world. Export promotion is very essential for the development of Indian economy. Hence the government of India has been adopting various export promotional measures for the promotion and development of marine products. Export Promotion measures includ7e various policy decisions, schemes, concessions, incentives facilities offered to the exporters. The Marine Product Export Development Authority was constituted in 1972 at Cochin for the overall development of marine product industry and promoting the export of marine products. The authority is concerned with regulation and growth of marine products. Special emphasizes is laid on maintaining quality of marine products, processing, packing, storing, shipment, marketing etc. The authority conducts fairs and exhibitions and also takes part in international fairs. The authority advices central government on all matters related to seafood industry and its exports. On a thorough study conducted in the previous chapter, some facts were identified. As mentioned earlier, as there are number of items under the marine products meant for export to different destinations, analysis has been done for those items and the following details has been found out: